ASYMMETRIC-SYNTHESIS OF (-)-(1R,2S)-CISPENTACIN AND RELATED CIS-2-AMINO AND TRANS-2-AMINO CYCLOPENTANE-1-CARBOXYLIC AND CYCLOHEXANE-1-CARBOXYLIC ACIDS - Davies, S; Ichihara, O; Lenoir, I; Walters, I (1994)
The antifungal antibiotic (-)-(1R,2S)-2-aminocyclopentane-1-carboxylic acid (cispentacin) 8 and its cyclohexane homologue 14 have been prepared utilizing the highly stereoselective conjugate addition of homochiral lithium N-benzyl-N-α-methylbenzylamide 5. The corresponding trans-β-amino acids 10 and 16 were also prepared via the selective epimerization of the cis-β-amino ester conjugate addition products.